2019
DOI: 10.1182/blood-2019-123995
|View full text |Cite
|
Sign up to set email alerts
|

An Adaptive Design Study to Evaluate the Efficacy, Safety and Pharmacokinetics of Emapalumab in Adult Patients with Non-Primary Hemophagocytic Lymphohistiocytosis

Abstract: Background: Secondary hemophagocytic lymphohistiocytosis (sHLH) is a rare, life-threatening syndrome which may develop on the background of several clinical conditions (e.g., autoimmune disease, infection or malignancy) and is characterized by uncontrolled hyperinflammation. Preclinical data have shown the central role of interferon-gamma (IFNγ) in the pathogenesis of this disease (Strippoli et al. 2012; Prencipe et al. 2018), and observational studies confirm the presence of an IFNγ signature in sHLH (data on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A promising analysis of 7 patients with EBV-HLH who were treated with nivolumab every 3 weeks showed that 5 of these patients had CR [26]. Other compounds in clinical trials are the JAK 1/2 inhibitor ruxolitinib [27] and the IFNγ-neutralizing antibody emapalumab [28], which has already received FDA approval for primary HLH. The ultimate treatment of refractory EBV-HLH remains allogeneic stem cell transplantation [29].…”
Section: Discussionmentioning
confidence: 99%
“…A promising analysis of 7 patients with EBV-HLH who were treated with nivolumab every 3 weeks showed that 5 of these patients had CR [26]. Other compounds in clinical trials are the JAK 1/2 inhibitor ruxolitinib [27] and the IFNγ-neutralizing antibody emapalumab [28], which has already received FDA approval for primary HLH. The ultimate treatment of refractory EBV-HLH remains allogeneic stem cell transplantation [29].…”
Section: Discussionmentioning
confidence: 99%